The decline of race in American physical anthropology - Lieberman, Leonard; Kirk, Rodney C.; Corcoran, Michael (Polskie Towarzystwo Antropologiczne, 2003)
This paper is a review of how and why the race concept has changed in the United States during the 20th century. In the 19th century the concept of race provided the unchallenged folk taxonomy and the prevailing scientific paradigm for placing human biological and cultural variation into categories called races. At the height of the eugenic and anti-immigration movement of the early decades of the 20th century, Boas and his students began the critique of racism and aspects of the race concept. In the early 1950s Washburn proposed that the modern synthesis replace race typology with the study of processes and populations. In the 1960s new data on clinal genetic gradations provided tools for studying human variation while challenging the race concept. We present the several kinds of ducumentaion of the decline of the race concept over 20th century, and place the above changes in the context of the essential development of new genetic evidence. We also relate the decline of race to historical developments, the growth of the culture concept, and the biographies of the participants. We reject political correctness and view science as a self-correcting endeavor to relate concepts to the empirical world.
Keywords: race; cline; population; Boas; Washburn